Primary Sacral Non-Hodgkin’s Lymphoma: A Case Report - Dinh Thi Phuong Hoai; Vo Ba Tuong, Naoyuki Noda, Huynh Nguyen Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2020)
Primary sacral lymphoma is rare, accounting for approximately 5-7% of all spinal tumors. It typically presents with atypical symptoms such as back pain and radiculopathy. This report presents a clinical case of primary lymphoma in a 74-year-old woman who experienced pain and numbness in her legs. CT and MRI revealed a mass measuring 5.6 x 9.5 x 7.7 cm, with histopathology confirming Non-Hodgkin’s lymphoma of B cell lineage. The aim of this report is to highlight this rare case of primary sacral Non-Hodgkin’s lymphoma.